2013
DOI: 10.1093/cvr/cvt230
|View full text |Cite
|
Sign up to set email alerts
|

Zoledronate attenuates angiotensin II-induced abdominal aortic aneurysm through inactivation of Rho/ROCK-dependent JNK and NF-κB pathway

Abstract: Zoledronate-attenuated Ang II induced AAA formation by suppression of MMP-2 activity and suppressed vascular inflammation and Ang II-induced Rho/ROCK activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
41
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 42 publications
5
41
0
Order By: Relevance
“…A recent study showed that inhibitor of nuclear factor kappa-B kinase epsilon (IKKe) is related to vascular inflammation, which accounts for its important role in the atherosclerosis, and it also has a potential relationship with the hypertension [13]. The role of IKKe in the development of atherosclerosis was further verified in our previous investigation, and recent studies have confirmed that atherosclerosis is a risk factor for AA [1,6,13].…”
Section: Introductionsupporting
confidence: 66%
See 1 more Smart Citation
“…A recent study showed that inhibitor of nuclear factor kappa-B kinase epsilon (IKKe) is related to vascular inflammation, which accounts for its important role in the atherosclerosis, and it also has a potential relationship with the hypertension [13]. The role of IKKe in the development of atherosclerosis was further verified in our previous investigation, and recent studies have confirmed that atherosclerosis is a risk factor for AA [1,6,13].…”
Section: Introductionsupporting
confidence: 66%
“…The role of IKKe in the development of atherosclerosis was further verified in our previous investigation, and recent studies have confirmed that atherosclerosis is a risk factor for AA [1,6,13]. Matrix metalloproteinase-2 (MMP-2), a downstream of IKKe, is widespread and responsible for extracellular collagen degradation and remodelling [8].…”
Section: Introductionsupporting
confidence: 63%
“…However, in contrast to Tsai et al, we found no suppression of AAA ( Figure XX in the online-only Data Supplement). 4,33,34 These differing results may be because of the amount of ZA binding to CaPO 4 . We also speculate that the absence of a bisphosphonate effect is related to the lack of overt arterial calcification in aneurysms in this model.…”
Section: Discussionmentioning
confidence: 99%
“…Nistala et al also reported negative results for bisphosphonate on aneurysm progression in Marfan syndrome using Fbn1 (mgR/ mgR) mice. 33,35 Because Fbn1 mice more closely mimic connective tissue disorders, such as Marfan syndrome, we think that the underlying mechanism in this model differs from the pathophysiology of the traditional AAA model.…”
Section: Discussionmentioning
confidence: 99%
“…It is generally reported that phosphorylation of ERK and JNK is increased in AngII-induced AAA tissues, whereas p38 phosphorylation is not changed in AAA walls. 31 However, it is reported that phosphorylation of ERK and JNK vary by the region of aorta. 32 Because we used whole aortic tissues to examine protein expression, this apparent discrepancy may have occurred because of these concerns.…”
Section: Sawada Et Al Iron and Abdominal Aortic Aneurysm 1513mentioning
confidence: 99%